The immunoproteasomes are key to regulate myokines and MHC class I expression in idiopathic inflammatory myopathies. (December 2016) - Bhattarai, Salyan; Ghannam, Khetam; Krause, Sabine; Benveniste, Olivier; Marg, Andreas; de Bruin, Gerjan; Xin, Bo-Tao; Overkleeft, Hermen S.; Spuler, Simone; Stenzel, Werner; Feist, Eugen
Abstract: Idiopathic inflammatory myopathies (IIMs) are diseases with muscle weakness, morphologically characterized by inflammatory infiltration and increased expression of MHC class I molecule on myofibers. Immunoproteasome, as a proteolytic complex that shapes the repertoire of antigenic peptides, has been previously demonstrated to be over-expressed in IIMs at mRNA level. In this study, we investigated the expression and the function of the immunoproteasome in IIMs in more detail. As shown by immunofluorescence staining, expression of relevant players of the immunoproteasome was detectable in the inflamed skeletal muscle tissue from IIM patients. In fact, two subunits of the immunoproteasome, β1i or β5i were upregulated in sporadic inclusion body myositis, immune-mediated necrotizing myopathies and dermatomyositis muscle biopsies and co-localized with the MHC class I expressing myofibers. Double immunofluorescence revealed that both myofibers and muscle infiltrating cells, including CD8 + T-cells and CD68  +  macrophages in IIMs expressed β1i or β5i. In addition, we have also investigated the role of the immunoproteasome in myoblasts during in vitro inflammatory conditions. Using human primary myoblasts cultures we found that pro-inflammatory cytokines, TNF-α or IFN-γ upregulate β1i or β5i. Selective inhibition or depletion of β5i amplified the TNF-α or IFN-γ mediated expression of cytokines/chemokines (myokines) in myoblasts. Furthermore, we demonstrated that specific inhibitors of β1i or β5i reduced the cell surface expression of MHC class I in myoblasts induced by IFN-γ. Taken together, our data suggest that the immunoproteasome is involved in pathologic MHC class I expression and maintenance of myokine production in IIMs. Thus, induction of the immunoproteasome was identified as a pathomechanism underlying inflammation in IIMs. Highlights: Idiopathic inflammatory myopathies muscle fibers induce immunoproteasome subunits. Immunoproteasome inhibition reduce surface expression of MHC-I molecule in myoblast. Immunoproteasome inhibition amplify inflammatory mediated myokine expression.